Proximal Tibial Reconstruction After Tumor Resection: A Systematic Review of the Literature. Issue 7 (July 2019) - Summers, Spencer H.; Zachwieja, Erik C.; Butler, Alexander J.; Mohile, Neil V.; Pretell-Mazzini, Juan
Abstract : Background: The proximal part of the tibia is a common location for primary bone tumors, and many options for reconstruction exist following resection. This anatomic location has a notoriously high complication rate, and each available reconstruction method is associated with unique risks and benefits. The most commonly utilized implants are metallic endoprostheses, osteoarticular allografts, and allograft-prosthesis composites. There is a current lack of data comparing the outcomes of these reconstructive techniques in the literature. Methods: A systematic review of peer-reviewed observational studies evaluating outcomes after proximal tibial reconstruction was conducted, including both aggregate and pooled data sets and utilizing a Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) review for quality assessment. Henderson complications, amputation rates, implant survival, and functional outcomes were evaluated. Results: A total of 1, 643 patients were identified from 29 studies, including 1, 402 patients who underwent reconstruction with metallic endoprostheses, 183 patients who underwent reconstruction with osteoarticular allografts, and 58 patients who underwent with reconstruction with allograft-prosthesis composites. The mean follow-up times were 83.5 months (range, 37.3 to 176 months) for the metallic endoprosthesis group, 109.4 months (range, 49 to 234 months) for the osteoarticular allograft group, and 88.8 months (range, 49 to 128 months) for the allograft-prosthesis composite reconstruction group. The mean patient age per study ranged from 13.5 to 50 years. Patients with metallic endoprostheses had the lowest rates of Henderson Type-1 complications (5.1%; p < 0.001), Type-3 complications (10.3%; p < 0.001), and Type-5 complications (5.8%; p < 0.001), whereas, on aggregate data analysis, patients with an osteoarticular allograft had the lowest rates of Type-2 complications (2.1%; p < 0.001) and patients with an allograft-prosthesis composite had the lowest rates of Type-4 complications (10.2%; p < 0.001). The Musculoskeletal Tumor Society (MSTS) scores were highest in patients with an osteoarticular allograft (26.8 points; p < 0.001). Pooled data analysis showed that patients with a metallic endoprosthesis had the lowest rates of sustaining any Henderson complication (23.1%; p = 0.009) and the highest implant survival rates (92.3%), and patients with an osteoarticular allograft had the lowest implant survival rates at 10 years (60.5%; p = 0.014). Conclusions: Osteoarticular allograft appears to lead to higher rates of Henderson complications and amputation rates when compared with metallic endoprostheses. However, functional outcomes may be higher in patients with osteoarticular allograft. Further work is needed using higher-powered randomized controlled trials to definitively determine the superiority of one reconstructive option over another. In the absence of such high-powered evidence, we encourage individual surgeons to choose reconstructive options based on personal experience and expertise. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.